Diversity, species richness distribution and centers of endemism of Lycianthes (Capsiceae, Solanaceae) in Mexico - Anguiano-Constante, Marco Antonio; Dean, Ellen; Starbuck, Thomas; Rodríguez, Aarón; Munguía-Lino, Guadalupe (Phytotaxa, 2021)
Spatial patterns of plant diversity matter. Identifying areas of high species richness and endemism are crucial for understanding the evolution of plant diversity and community assemblages as well establishing sustainablility and conservation priorities. Lycianthes is the third most species-rich genus in the Solanaceae with 187 taxa (152 species, 10 subspecies and 25 varieties) native to the Americas and Asia-Pacific region. However, the distributions of the taxa are uneven and usually concentrated along mountain ranges in the Neotropic. In Mexico, the main mountain chains are known as the Mexican Transition Zone (MTZ), so we expected the highest species richness and endemism to be found there. Our aims were twofold; first, to determine the Lycianthes species richness in Mexico; and second, to analyze the spatial patterns. We used 2305 georeferenced records obtained from specimens examined in herbaria, electronic specimen databases and specimens cited in the literature. Then, we analyzed species richness and endemism using a grid-cell of 50 × 50 km, political divisions, biogeographic provinces, vegetation types, and elevation. In addition, endemism was quantified using weighted endemism (WE) and corrected weighted endemism (CWE). In Mexico, there were 48 taxa of Lycianthes, which included 44 species and four varieties. Of these, 20 species and two varieties were endemic. We found 14 cells of high species richness and eight centers of endemism, all located across the MTZ. The pine-oak forest resulted in the richest plant community followed by the cloud forest along an elevational gradient of 1000–2000 m. Likewise, endemism was found within the pine-oak forest of the MTZ, between 1000–2000 m of elevation. The geological history and climatic conditions of the MTZ could explain the diversity of Lycianthes there.